Amplification and cloning of block 2 of the gene encoding Merozoite Surface Protein-1 (MSP-1) of Plasmodium falciparum isolated from Kokap, Yogyakarta - Elsa Herdiana Elsa Herdiana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Falciparum malaria remains a major public health problem in tropical and subtropical countries including Indonesia. The disease is caused by Plasmodium falciparum and spread by Anopheline mosquitoes. The widespread of Plasmodium which are resistant to antimalarial drugs and Anopheline mosquitoes which are resistant to insecticides have urged to look for alternative solutions including the development of protective vaccines. Several vaccine candidates have been studied, one of them is Merozoite Surface Protein-1 (MSP-1) which is expressed on the surface of merozoite. It was shown that this protein induces protective immune responses. Variation on the gene encoding MSP-1 of Plasmodium falciparum has been well documented but such data from Indonesia population have never been studied. Objective: The aim of this study is to amplify and clone MSP-1 gene of P. falciparum isolated from Kokap, Yogyakarta.Methods: Block 2 of the gene encoding MSP-1 was amplified by Polymerase Chain Reaction (PCR) and the PCR amplification products were cloned using pGEMÂ® -T vector and transformed into Escherichia coil JM 109.Result: From 19 PCR results, 3 were cloned and 10 colonies were picked up. Nine of 10 showed the MSP-1 gene insertion by PCR method.Conclusion: Block 2 of the gene encoding MSP-1 of P. falciparum isolated from Kokap, Yogyakarta was successfully amplified by PCR method. This study resulted in 9 recombinant plasmids which contained MSP-1 gene as the outcome of cloning and transformation into E.coli.Key words: P. falciparum - MSP-1 - PCR - Amplification - Cloning